'The communal' in school and indigenous radio: Evidence from the North of Argentina. (1st October 2017) - Belotti, Francesca; Siares, Emilse
The Argentinian Law 26.522 on Audiovisual Communication Services (currently under reform) aimed at democratizing the media arena by recognizing multiple actors such as community broadcasters, school and indigenous media, among others. According to the legal classification, community broadcasters were regulated as private non-profit media, despite having specific objectives, programming, organizational logic and economic conditions. Conversely, school and indigenous media merged into the public sector, even if they may act as community media. The article compares results arising from two research projects carried out in Northern Argentina through in-depth interviews with key informants from two indigenous radio stations and two school radio stations. The theoretical framework mainly draws on literature about community, alternative and popular communication. Results show that communities participate in such media foundation or management and that media content deals with cultural and political issues related to their interests or needs. Indeed, emerging features allow considering such broadcasters as community media.